2016
DOI: 10.1189/jlb.3a0116-028rr
|View full text |Cite
|
Sign up to set email alerts
|

Irgm1 is required for the inflammatory function of M1 macrophage in early experimental autoimmune encephalomyelitis

Abstract: The classically activated (M1) macrophage has been shown to play an indispensable role in experimental autoimmune encephalomyelitis (EAE), the animal model of multiple sclerosis (MS). However, most studies focus on the effect of macrophage on CNS demyelination of EAE; whether the M1 macrophage participates in early EAE and the molecular mechanism underlying remains unclear. Here, we showed that the immunity-related GTPase family member 1 (Irgm1), also known as LRG-47, was expressed in M1 macrophages of drainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Based on the high expression of IRGM in glioma (Figures A and 1B), we supposed that IRGM regulated the formation of glioma immune microenvironment by influencing M2 GAM polarization. Although other experimental system found the role of IRGM in M1 macrophage polarization during autoimmune disease (Xu et al, ), high IRGM expression is less likely related to M1 macrophage polarization because M2 macrophage phenotype are predominant among tumor immune microenvironment. On another hand, differences of signal pathway activation between tumor cells and macrophage may lead to different function of IRGM, which will be studied in our future work.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Based on the high expression of IRGM in glioma (Figures A and 1B), we supposed that IRGM regulated the formation of glioma immune microenvironment by influencing M2 GAM polarization. Although other experimental system found the role of IRGM in M1 macrophage polarization during autoimmune disease (Xu et al, ), high IRGM expression is less likely related to M1 macrophage polarization because M2 macrophage phenotype are predominant among tumor immune microenvironment. On another hand, differences of signal pathway activation between tumor cells and macrophage may lead to different function of IRGM, which will be studied in our future work.…”
Section: Discussionmentioning
confidence: 93%
“…Previous study reports, IRGM/Irgm1 is closely related to chronic infectious diseases or inflammatory bowel diseases (Song et al, ; Iida et al, ). In addition, Irgm1 regulates macrophage subset polarization and cytokines production under autoimmune disease environment (Xu et al, ). Therefore, we supposed that whether IRGM highly expressed in glioma is closely related to immunocytes of glioma patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of PI3K/Akt signaling in synovial macrophages from rheumatoid arthritis patients is associated with increased apoptotic cell death 56 . Akt activation in macrophages results in reduced severity in experimental autoimmune encephalomyelitis 57 . Akt signaling was implicated in neuroprotection after stroke 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that LRG-1, a kind of secretive glycoprotein, could serve as an efficient biomarker for predicting the prognosis of PDAC patients. LRG-1 has been proven to be associated with inflammation and autoimmune disease in the past few years [40, 41]. Shinzaki et al demonstrated that LRG-1 was a serum biomarker of mucosal healing in ulcerative colitis (UC) and serum LRG-1 concentrations in active UC patients was significantly higher than that in patients who had complete mucosal healing and deep remission [40, 42].…”
Section: Discussionmentioning
confidence: 99%